Risk of Microangiopathy in Patients with Epilepsy under Long-term Antiepileptic Drug Therapy - Chen, Nai-Ching; Chen, Chih-Hsin; Lin, Tsu-Kung; Chen, Shang-Der; Tsai, Meng-Han; Chang, Chiung-Chih; Tsai, Wan-Chen; Chuang, Yao-Chung (Frontiers in Neurology, 2018)
Background: Long-term antiepileptic drug (AED) therapy is considered a risk factor of atherosclerosis. Furthermore, the duration of therapy contributes to acceleration of large-vessel atherosclerosis. Therefore, in this study, we tested the hypothesis that long-term AED therapy plays a crucial role in the pathogenesis of microangiopathy in patients with epilepsy. Methods: We recruited 120 patients with epilepsy (age, 18–60 years) and 40 healthy controls. Optical coherence tomography (OCT) was used to measure the central macular thickness and diameters of the retinal artery and vein to evaluate atherosclerotic retinopathy; microalbumin and creatinine levels in urine were assessed to evaluate atherosclerotic nephropathy. In addition, high-sensitivity C-reactive protein (hs-CRP), lipid profiles, homocysteine, folate, uric acid, and body mass index were determined. Results: The ratio of urine albumin to creatine and OCT findings showed that patients with epilepsy had higher abnormal microalbuminuria and narrowing retinal vein diameters, respectively. Multiple linear regression analysis showed that increased triglyceride and hs-CRP levels might contribute to microalbuminuria. In addition, serum creatinine, duration of AED therapy, enzyme-inducing AED therapy, and duration of enzyme-inducing AED therapy were candidate risk factors for retinal vein narrowing. Conclusion: Patients with epilepsy are at a higher risk for microangiopathy presented as retinopathy and nephropathy. Long-term AED therapy, particularly with enzyme-inducing AEDs; high triglyceride levels, and inflammatory processes play an important role in the development of microangiopathy in patients with epilepsy.